Observations on Propagation and Growth of Poplar (Populus deltoides Clone G-3) - Sharma, T. C.; Bardoloi, D. N. (Indian Forester, 1986)
Stem cuttings of Poplar (Populus delroides Clone G-3) were tried under different seasons. The highest percentage of sprouting (96 25) and survival (75.50) of the cuttings was observed, while the cuttings were made and planted during the months from December to February. The culting taken one-third part from the bottom performed better than those taken from the middle one-third, which did better than those taken from the top one-third part of the plants. Various growth parameters recorded for four years showed good growth of Poplar under the agromatic conditions of Jorhat.